HUBUNGAN ANTARA FREKUENSI PENGGUNAAN GADGET DENGAN KETERAMPILAN INTERAKSI SOSIAL PADA ANAK PRASEKOLAH - Sundari, Sri (Yayasan Healing and Healthcare Education, 2024)
This study aims to explore the relationship between the frequency of gadget use and social interaction skills in preschool children. Utilizing a quantitative analytic design with a cross-sectional approach, the research collected data from preschoolers to analyze the impact of gadget use frequency on their social skills. Data were gathered through questionnaires and direct observations, and analyzed to determine the significance of the relationship between gadget usage duration and social interaction skills. The results indicate that longer gadget use is negatively associated with social interaction skills; children who use gadgets for extended periods exhibit lower social skills compared to those with shorter gadget usage durations. The p-value of 0.002 confirms the statistical significance of this relationship. The findings underscore the importance of limiting gadget use to support healthy social development in preschoolers and highlight the need for active parental involvement in managing technology use. This study provides valuable insights for developing policies and practices that promote a balance between gadget use and social interaction in early childhood.